The fingerprints of photoionization and shock-ionization in two CSS sources. - Reynaldi, María Victoria (2016)
We investigate the ionization state of the extended emission-line regions (EELRs) around two compact steep-spectrum (CSS) radio galaxies, 3C 268.3 and 3C 303.1, in order to identify the contribution of photoionization and shock-ionization. We perform a new spectroscopical (long-slit) analysis with GMOS/Gemini with the slit oriented in the radio-jet direction, where outflows are known to exist. The [Ne V] λ3426 emission is the most interesting feature of the spectra and the one key to breaking the degeneracy between the models: since this emission-line is more extended than He II, it challenges the ionization structure proposed by any photoionization model, also its intensity relative to H β does not behave as expected with respect to the ionization parameter U in the same scenario. On the contrary, when it is compared to the intensity of [O II] λ3727/H β and all these results are joined, the whole scenario is plausible to be explained as emission coming from the hot, compressed, shocked gas in shock-ionization models. Although the model fitting is strongly sensitive to the chosen line ratios, it argues for the presence of external and strong ionizing fields, such as the precursor field created by the shock or/and the AGN radiation field. In this paper, we show how AGN photoionization and shock-ionization triggered by jet–cloud interaction work together in these EELRs in order to explain the observed trends and line-ratio behaviours in a kinematically acceptable way.